TATA KELOLA PASAR TRADISIONAL DI KOTA PEKANBARU - Tambunan, Beriman; ", Mayarni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
So far, the market 's sector in Pekanbaru is not maximal executed, so that still has no a great contribution to increase the region economic's growth. Traditional market can not defeat the expansion of modern markets, indeed. Whereas the traditional market is more strategic to be accessed by people in this case and also we know that traditional market is one of the reached place by a low-economic-doer which occupied in majority level. A good and professional market's management could increase the competitiveness of the traditional market and increase the economics matters. To push the professional market's management in Pekanbaru City, it needs a market's management guideline. This guideline is expecting to be a good references for the market's managers. The Purpose of this research is to know and analyse how to manage the traditional market in Pekanbaru City and also the elements which influencing that system management.This research is using a descriptive-qualitative method which it'd explicate and detail according to the facts. Then, the theory of this research is A Basic Functions of Management George R. Terry in Manullang (2008). He defined the basic functions of management are consists of Planning, Organizing, Actuating and Controlling. Datas are collected by the observation and interview. The Analyse technique is using a descriptive-qualitative method.After the research it found that the realization of system management of the traditional market in Pekanbaru City wasn't implemented well and too far from the expectation. One of the matter is because the lack of policy and the controlling on market's system management from the government and also it caused by the lack of awareness of the societies and the traders to obey the regulations about the market's activity in accordance with the regulations of law in effect. There are many reasons why, like the human resource, the financial resource, the infrastructures, and also the communication.Keyword: System management, Traditional Market, Planning, Organzing, Actuating and Controlling